Dandelion (Taraxacum mongolicum) Extract Alleviated H2O2-Induced Oxidative Damage: The Underlying Mechanism Revealed by Metabolomics and Lipidomics - Yannan Chen; Siyuan Fei; Xiaoting Yu; Mingqian Tan (Foods, 2023)
Dandelion has received wide attention in food and medicine fields due to its excellent antioxidant properties. Nonetheless, the underlying mechanism of this action has not yet been fully clarified, particularly at the metabolic level. Herein, the effects of dandelion extract (DE) on H2O2-induced oxidative damage was investigated. The results indicate that the DE alleviated H2O2-induced cell damage (increased by 14.5% compared to H2O2 group), reduced the reactive oxygen species (ROS) level (decreased by 80.1% compared to H2O2 group), maintained the mitochondrial membrane potential (MMP) level, and increased antioxidant-related enzyme activities. Importantly, the metabolic response of PC12 cells indicates that H2O2 disturbed phospholipid metabolism and damaged cell membrane integrity. In addition, energy metabolism, the central nervous system, and the antioxidant-related metabolism pathway were perturbed. In contrast, DE rescued the H2O2-induced metabolic disorder and further alleviated oxidative damage. Collectively, these findings provide valuable stepping stones for a discussion of the mechanism and show the promise of DE as a suitable additive for functional food products.